Resource elements of the national blue economic system and their development mechanisms: a case study of China - Qi, Xiaofei (Frontiers in Marine Science, 2025)
As a complex system involving intra- and interrelevance among multiple economic entities, the core of blue economic development consists of identifying key entities and their relevance structures that play a significant role in resource allocation within the system. The structural adjustment of blue industries, the enrichment of blue product baskets, the management decisions of blue firms, and the export positioning of blue provinces will make the system drive dynamic changes. Therefore, from the perspective of relevance theory, this paper first analyzes the key factors affecting the stability of the national blue economic system based on blue industry relevance, blue product relevance, blue firm relevance, blue province relevance, and cross-agent relevance. Second, the development mechanism of the national blue economic system is qualitatively explored based on the intra-agent relevance at a single level and the interagent relevance at a cross level. Finally, an example from China is used to guide its blue economy in practice. This example can serve as the premise and foundation for a country to achieve blue growth, promote the common development of key agents in the blue economy, and provide a scientific basis for a country to systematically formulate blue economic development policies.